ANALISIS PEMANTAUAN DAN PENGONTROLAN AQUASCAPE BERBASIS WEB DAN ANDROID UNTUK MENENTUKAN KUALITAS AIR DENGAN TEHNIK FUZZY LOGIC - Sulaiman Djaohar (LPPM IAI As-Siddiq Kie Raha Maluku Utara, 2022)
Many aquascape cultivators have difficulty in achieving the requirements of integrating ornamental fish and aquatic plants in checking the quality of aquascape. then the water quality needs to be determined to meet these requirements in aquascape cultivation. along with the progress of current technology, manual monitoring and control of Aquascape can already be automated and supported by remote control and monitoring. With the help of a microcontroller in determining the good water quality can be examined and determined the good water quality in aquascape in determining the temperature, pH and turbidity of the water by using fuzzy logic techniques. The control becomes more efficient with the help of web and android as a remote interface that can help the farmers monitoring their aquascape.